Environmental-friendly one-step fabrication of tertiary amine-functionalized adsorption resins for removal of benzophenone-4 from water. (1st December 2018) - Zhou, Xia; Yang, Ye; Li, Chao; Yang, Zhen; Yang, Weiben; Tian, Ziqi; Zhang, Limin; Tao, Tao
Abstract: 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid with a trade name of benzophenone-4, a typical anti-UV product, is increasingly detected in real aqueous environment. Few literature using cost-effective adsorption means with enough high adsorption capacity for the removal of benzophenone-4 is available. In this work, a series of novel tertiary amine-functionalized crosslinking polymeric resins, synthesized using different proportions of raw materials including 2-dimethylamino ethyl methacrylate as the monomer, divinylbenzene as the crosslinking reagent and toluene as the pore-forming reagent, were employed for the adsorption of benzophenone-4. During the synthesis process, an environmental-friendly one-step fabrication method, following the concept of cleaner production, was established for the reduction of unnecessary derivatization steps, extra pollution risk, costs and time. Among these resins, the optimal one with relatively larger pore diameter, larger specific surface area, and fewer inner defects, exhibited the highest adsorption capacity of 154 mg/g. Such a value was notably larger than several frequently reported commercial adsorbents, including activated carbon, ion exchange resins and macroporous resins. The performance of the resin not only owned strong resistance against influences of coexisting natural organic matter and inorganic ions, but also bore reuse without much capacity loss after six adsorption-desorption cycles. Adsorption interfacial interactions were studied, via both experimental analyses and chemical calculations. Electrostatic attraction between tertiary amine of the resin and SO3 - of benzophenone-4 played a leading role during adsorption. Graphical abstract: Image 1 Highlights: Facile one-step synthesis of tertiary amine-functionalized polymer resins is achieved. The novel resins own higher Q e of BP-4 than commercial adsorbents. Strong resistance against impacts of coexisting NOM and inorganic ions is found. The optimized resin is reusable after six adsorption-desorption cycles. Electrostatic attraction plays a dominant role in adsorption.